On the issue of allocation of a risk group for the presence of mental disorders in the practice of cardiology department - M. V. Dorofeikova; S. F. Zadvoryev; N. N. Petrova; A. A. Yakovlev (Acta Biomedica Scientifica, 2017)
Differential diagnosis of somatic and somatoform pathology is a pressing issue in general practice. The aim of this study was to develop an algorithm for identification of the patients with indications for psychiatrist's consultation and possible psychotropic therapy at the stage of admission to multi-disciplinary hospital. Material and methods. Regression analysis of data of 1031 patient hospitalized in the cardiology department of a multiprofile hospital was done with the aim of identifying factors determining the recommendation for receiving psychotropic therapy at discharge. Results. An algorithm for allocation among patients of cardiological profile individuals that require a multidisciplinary approach to treatment involving experts in the field of mental health is proposed. Factors included in the formula were labile or paroxysmal hypertension, the number of associated (non-cardiological) diagnosis, female gender and heart rate or heart rhythm disorders with the debut at the age below 55 or 50 years: I = 8 х L + D + 3 х F + 3 (6) х H. Conclusion. The revealed pattern may be useful in the clinic of internal diseases for screening of patients with a high contribution of the emotional state the severity of the condition. The doctors of the hospitals of somatic (therapeutic) profile should pay more attention to the psycho-emotional condition of patients with labile hypertension, early onset of cardiac arrhythmias, and large number of comorbidities. Patients that meet the criteria are likely to need a consultation of a psychotherapist or psychiatrist because of the presence of psychosomatic or other mental disorders.